Aerodynamic design and multi-dimensional performance optimization of supercritical CO2 centrifugal compressor. (15th November 2021) - Xia, Wenkai; Zhang, Yicen; Yu, Haibin; Han, Zihao; Dai, Yiping
Highlights: A SCO2 simple regenerative Brayton cycle used in SLFR is proposed. One-dimensional analysis code is developed to design SCO2 compressor. Optimization is implemented to improve isentropic efficiency using 1D code. Optimization is conducted on impeller blade through three-dimensional CFD. Abstract: This paper dedicates to develop a systematic approach of design and multi-dimensional performance optimization of the Supercritical carbon dioxide (SCO2 ) compressor. A 5 MW SCO2 simple regenerative cycle used in small scale lead-cooled fast reactor (SLFR) was firstly proposed and simulated to define the operation condition of SCO2 compressor. Under the inlet and outlet condition of 305.15 K/7.56 MPa and 22 MPa, isentropic efficiency and mass flow rate of 80% and 69.88 kg·s −1 respectively was obtained. Secondly, a single stage centrifugal compressor was applied as the SCO2 compressor and one-dimensional (1D) design based on self-developed code was conducted to determine the basic geometry of the compressor, the code was verified with experiments and shows satisfactory accuracy. Additionally, CFD analysis was carried out to validate the results of 1D design and also shows good agreement. Then, three one-dimensional optimizations, two single objective optimizations using Particle Swarm Optimization (PSO) and one multi-objective optimization using Genetic Algorithm (GA), on aerodynamic efficiency of the SCO2 centrifugal compressor were performed based on 1D design code, five crucial parameters with ± 5% variation range were optimized. The 1D optimization results show that the isentropic efficiency received an improvement of about 5 percentage points compared to that of 1D design. Lastly, three-dimensional optimization concentrated on the blade profile of impeller were conducted on a fully automatic optimization platform to further improve the isentropic efficiency of SCO2 centrifugal compressor. Wrap angle and the leading and trailing edge of the main blade were optimized. Two optimal impellers with wrap angle in the range of + 5% and −5% were obtained respectively, the former impeller got the highest pressure ratio, while the latter one gained a higher isentropic efficiency but the lowest pressure ratio over the whole operation range.